The necessity for specific legislation in controlling flood disasters in Malaysia / Nurul Jannah Mustafa Khan - Mustafa Khan, Nurul Jannah (2014)
This article which is drawn from an ongoing research on the laws relating to flood disaster attempts to examine the necessity of a specific legislation to govern flood disaster management system. This involves, amongst others, an examination on the National Security Council Directive No. 20, and also other legislations such as the Street, Drainage and Building Act 1974, the Drainage Works Act 1954 and Land Conservation Act 1960 that play a part during the occurrence of flood. In this article, a comparative analysis with the legal position in Queensland, Australia through their Disaster Management Act 2003 is made as it would provide some guidelines for Malaysia to learn in providing a specific legal framework governing flood system to effectively manage flood.